Geography And Social Movement : Comparing Antinuclear Activism in the Boston Area - Miller, Byron A., 1957- (University of Minnesota Press, 2000)
Byron A. Miller directly addresses the implications of space, place, and scale in social movement mobilization, and then demonstrates their significance in a detailed comparative analysis of peace movements in three municipalities around Boston.
Keywords: Social change.; Social movements -- Massachusetts -- Boston.; Social movements.; Antinuclear movement -- Massachusetts -- Boston.; Mouvements sociaux -- Massachusetts -- Boston.; Mouvements sociaux.; Mouvement antinucléaire -- Massachusetts -- Boston.; social movements.; SOCIAL SCIENCE -- Human Geography.; Antinuclear movement; Social change; Social movements; Massachusetts -- Boston